Recent advances in modified commercial separators for lithium–sulfur batteries. Issue 15 (14th March 2023) - Kim, Andrew; Oh, Seok Hyeon; Adhikari, Arindam; Sathe, Bhaskar R.; Kumar, Sandeep; Patel, Rajkumar
Abstract : Lithium–sulfur batteries (LSBs) are one of the most promising next-generation batteries because they have higher theoretical capacities, lower cost, and smaller environmental impact than lithium-ion batteries (LIBs). Abstract : Lithium–sulfur batteries (LSBs) are one of the most promising next-generation batteries because they have higher theoretical capacities, lower cost, and smaller environmental impact than lithium-ion batteries (LIBs). However, one of the main issues preventing widespread LSB adoption is its low cycle stability due to the formation and diffusion of intermediate lithium polysulfides (LiPSs). Some of the most cutting-edge advancements of LSBs address this issue by using functional separators modified from commercial polyolefin separators used in most LIBs. Popular and promising modifiers include (a) many functionalized or conducting polymers, (b) different carbon nanostructures like graphene or carbon nanotubes, (c) covalent–organic or metal–organic frameworks, and (d) various inorganic modifiers like metal oxides and MXenes. This review analyzes the latest insights into designing and fabricating modified polyolefin membranes that minimize polysulfide shuttling in LSBs. Other benefits, including enhanced rate capability, specific capacity, sulfur utilization, electrolyte wettability, Li-ion conductivity, thermal resilience, and structural integrity, are also discussed.